Plagiarism and the Withdrawal of a Degree: A Case Study Analysis - Steyn, Renier; Mokgalong, Mahlo; Nel, Jo; Williams, Adri (Issues in Social Science, 2024)
This case study delves into a complex instance of plagiarism within academia, focusing on the withdrawal of a graduate’s degree due to allegations of extensive copy-and-pasting in a mini-dissertation’s literature review section. The study examines the broader implications of plagiarism for scholarly integrity, educational institutions, and the recommendations proposed to address such misconduct.